Quantitative ELISAs for serum soluble LHCGR and hCG-LHCGR complex: potential diagnostics in first trimester pregnancy screening for stillbirth, Down's syndrome, preterm delivery and preeclampsia - Chambers Anne E; Griffin Christopher; Naif Samantha A; Mills Ian; Mills Walter E; Syngelaki Argyro; Nicolaides Kypros H; Banerjee Subhasis (BMC, 2012)
Abstract Background Soluble LH/hCG receptor (sLHCGR) released from placental explants and transfected cells can be detected in sera from pregnant women. To determine whether sLHCGR has diagnostic potential, quantitative ELISAs were developed and tested to examine the correlation between pregnancy outcome and levels of serum sLHCGR and hCG-sLHCGR complex. Methods Anti-LHCGR poly- and monoclonal antibodies recognizing defined LHCGR epitopes, commerical anti-hCGbeta antibody, together with recombinant LHCGR and yoked hCGbeta-LHCGR standard calibrators were used to develop two ELISAs. These assays were employed to quantify serum sLHCGR and hCG-sLHCGR at first trimester human pregnancy. Results Two ELISAs were developed and validated. Unlike any known biomarker, sLHCGR and hCG-sLHCGR are unique because Down's syndrome (DS), preeclampsia and preterm delivery are linked to both low (less than or equal to 5 pmol/mL), and high (equal to or greater than 170 pmol/mL) concentrations. At these cut-off values, serum hCG-sLHCGR together with PAPP-A detected additional DS pregnancies (21%) which were negative by free hCGbeta plus PAPP-A screening procedure. Therefore, sLHCGR/hCG-sLHCGR has an additive effect on the current primary biochemical screening of aneuploid pregnancies. More than 88% of pregnancies destined to end in fetal demise (stillbirth) exhibited very low serum hCG-sLHCGR(less than or equal to 5 pmol/mL) compared to controls (median 16.15 pmol/mL, n = 390). The frequency of high hCG-sLHCGR concentrations (equal to or greater than 170 pmol/mL) in pathological pregnancies was at least 3-6-fold higher than that of the control, suggesting possible modulation of the thyrotropic effect of hCG by sLHCGR. Conclusions Serum sLHCGR/hCG-sLHCGR together with PAPP-A, have significant potential as first trimester screening markers for predicting pathological outcomes in pregnancy.